The Relationship of Sociodemographic Characteristics Toward the Level of Vitamin Swamedication Knowledge in the Community at A Pharmacy X, Cirebon Regency - L, Efriani; S, Nurlaela; A, Irawan; TA, Putra; I, Hadi; S, Marfuati (Jurnal Medisci, 2024)
Knowledge of a person's health determines behavior when seeking treatment. Vitamin self-medication is a self-medication activity that uses vitamins needed by the body for normal metabolic processes and growth. This study was conducted to determine the relationship between sociodemographic characteristics and the level of knowledge of vitamin self-medication at Apotek X, Cirebon Regency. The method used is a cross sectional method with a sampling technique of consecutive sampling as many as 80 respondents. The data were analyzed by Spearman test using Statistical Product And Service Solutions (SPSS) version 25. The results showed the sociodemographic characteristics of the majority of respondents aged 26-45 years (44%), female gender (65%), education level SMA/SMK/MA ( 49%), and 55% of other occupations. Having sufficient knowledge level (63%) and having a relationship between sociodemographic characteristics in the form of education level with knowledge level of vitamin self-medication with pValue = 0.015 (p<0.05). The conclusion of the study is that there is a significant relationship between the level of education and the level of knowledge of vitamin self-medication